2018
DOI: 10.1016/j.devcel.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Blood-Brain Barrier Adapts to Cell Growth by Unfolding of Pre-existing Septate Junctions

Abstract: Graphical Abstract Highlights d Septate junction (SJ) proteins are stable for days d SJ strands are prefigured during embryogenesis and are unfolded during larval stages d The G-protein coupled receptor Moody suppresses interdigitating cell-cell protrusions d Moody promotes formation of continuous SJ strands SUMMARYThe blood-brain barrier is crucial for nervous system function. It is established early during development and stays intact during growth of the brain. In invertebrates, septate junctions are the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 57 publications
6
63
0
Order By: Relevance
“…Understanding how basolateral proteins maintain apical-basal polarity requires approaches to explore their dynamic behavior, which is intimately connected to their function. Dlg and Scrib mobility has been previously studied in the context of septate junctions (Babatz et al, 2018;Oshima and Fehon, 2011). We now compared the dynamics of the basolateral determinants in the lateral domain and dissected the mechanisms of Lgl association to the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how basolateral proteins maintain apical-basal polarity requires approaches to explore their dynamic behavior, which is intimately connected to their function. Dlg and Scrib mobility has been previously studied in the context of septate junctions (Babatz et al, 2018;Oshima and Fehon, 2011). We now compared the dynamics of the basolateral determinants in the lateral domain and dissected the mechanisms of Lgl association to the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Moody‐dependent formation of actin‐rich structures along the lateral membrane of the subperineurial glia requires myosin activation and controls blood–brain barrier function (Hatan, Shinder, Israeli, Schnorrer, & Volk, ). Homozygous moody mutants, however, are viable and have only a mildly affected blood–brain barrier (Stork et al, ) due to a compensatory formation of interdigitating cell‐cell protrusions, resembling the evolutionary ancient barrier type found in primitive vertebrates or invertebrates such as cuttlefish (Stork et al, 2018; Babatz, Naffin & Klämbt, ).…”
Section: Surface Gliamentioning
confidence: 99%
“…In Drosophila, septate junction complexes show an amazing stability and exist without major remodeling for several days. To cope with the enormous growth of the subperineurial glial cells during development, most septate junctions are preassembled in a folded manner already during embryonic stages which are then stretched out during larval growth (Babatz, Naffin & Klämbt, 2018). To date, more than 20 membrane or membrane-associated proteins are known including the conserved core components NeurexinIV/CASPR and Neuroglian/ NF150 (Faivre-Sarrailh et al, 2004;Hall et al, 2014;Jaspers et al, 2012;Nilton et al, 2010;Oshima & Fehon, 2011;Syed, Krudewig, Engelen, Stork, & Klämbt, 2011;Wu & Beitel, 2004).…”
Section: Subperineurial Glial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…One well-studied SJ protein in SPG, Moody, has been shown be required for SJ formation Schwabe et al, 2005), but previous work (Stork et al, 2008) from the group reporting the current study has shown that animals lacking Moody survive with only mild BBB permeability. In moody mutant animals, Babatz et al (2018) show that SJs are established at the early stages but appear less corrugated, more fragmented, and with pre-assembled SJ components frequently found outside of SJ strands. How is barrier function preserved despite these poorly constructed SJs?…”
mentioning
confidence: 91%